2011
DOI: 10.1159/000322360
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Treatment for Anorexia Nervosa: A Meta-Analysis of Standardized Mean Change

Abstract: Background: For the German treatment guidelines for eating disorders, the literature on psychological treatment of anorexia nervosa (AN) was reviewed systematically. As a common meta-analysis of randomized clinical trials proved to be impossible, a review of all available clinical trials was conducted, statistically integrating standardized mean change scores. Research questions comprised differential effects of therapeutic techniques and settings as well as determining which weight gains could be expected. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 149 publications
6
53
0
4
Order By: Relevance
“…No indications are available on a stage-oriented use of therapeutic tools, such as psychotherapy [135]. …”
Section: Resultsmentioning
confidence: 99%
“…No indications are available on a stage-oriented use of therapeutic tools, such as psychotherapy [135]. …”
Section: Resultsmentioning
confidence: 99%
“…The treatment studies did demonstrate reduced costs for shorter inpatient hospital admissions compared with longer inpatient hospitalization [34] and reduced costs for partial hospitalization [22] and outpatient treatment [35] compared to inpatient care. On the basis of treatment outcome it is not possible to recommend one treatment setting over another, however, based on the consistent finding of increased costs it is difficult to support the use of inpatient treatment in AN in the absence of medical instability or other risk issues and even in these circumstances difficult to support inpatient treatment beyond medical stabilization [15,17,34] .…”
Section: Discussionmentioning
confidence: 99%
“…Hospitalization of patients with AN for the management of acute medical instability (e.g., hypothermia, hypotension, electrolyte abnormalities and cardiac arrhythmias) is thought to be essential in preventing mortality associated with AN [8,15] , however, the benefits of inpatient weight restoration and the assumption that hospital is the best venue for refeeding once medical stability has been achieved remain unsupported by current evidence [16] . This problem is highlighted by a recent meta-analysis of 57 clinical trials in AN that found no difference in treatment effects based on the style of therapy or treatment setting [17] . Treatment settings for AN include inpatient, partial hospitalization (also known as day hospital care) and outpatient.…”
Section: Introductionmentioning
confidence: 99%
“…Anorexia nervosa is characterized by extremely low body weight and is associated with a number of secondary complications due to malnourishment and/or complications due to vomiting or laxative misuse [8]. At present, pharmacotherapy with antipsychotics is not recommended according to treatment guidelines [9,10,11] and psychotherapeutic treatment approaches appear to be more promising [12,13]. However, the number of prescriptions of second-generation antipsychotic drugs (SGAs) to anorectic patients has substantially increased over the last years [14].…”
Section: Introductionmentioning
confidence: 99%